Partisanship in a young democracy: Evidence from Ghana - Alexander Stöcker (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2021)
While past studies have put forward many reasons why partisanship in young African democracies should be considered weak and meaningless, this paper casts doubt on this notion by presenting evidence that suggests the presence of strong and stable patterns of partisanship in ordinary citizens. Based on survey data from Ghana, I exploit the variation introduced by the political turnovers of 2008 and 2016, estimating a partisan divide for a wide range of perceptions and attitudes. The results suggest that partisanship is both meaningful and prompts motivated reasoning among citizens, while also being indicative of increased polarization and thus a potential threat to effective governance. Furthermore, the analysis of attitudes towards democratic principles uncovers a worrying double standard that could negatively affect efforts towards the consolidation of democracy. A simple heterogeneity analysis reveals that while partisan identities seem to exist alongside ethnic identities, the latter still strongly determines the strength of party attachment in Ghana. Future research on political behavior needs to acknowledge the presence of these partisan motives and continue to investigate the impact of partisanship on the further development of democratic institutions in African democracies.
Keywords: 330; Partisan Divide; Public Opinion; Democratization; Africa; Ghana